The Potential for Industrial Tourism Development in Ukraine: Kryvyi Rih Case Study - Gorina, Ganna O. (Konwersatorium Wiedzy o Mieście, 2022)
The aim of the article is to investigate the industrial tourist potential of the city of Kryvyi Rih based on the identification and description of its industrial heritage. The potential for industrial tourism development in Kryvyi Rih as a city with a powerful base of active industrial facilities and heritage sites is revealed. Attention is focused on the importance and necessity of using its this potential for tourism development by declaring this goal in medium and long-term development programs and strategies. Examples of using the city’s industrial heritage as tourist attractions are given. Problems and prospective directions for industrial tourism development in Kryvyi Rih are highlighted.